EPISTEMOLOGI AL-ASRAM: Dalam Kitab Na>Sikh Al-H}Adi>S| Wa Mansu>Khuh - Nurul Hakim (Dialogia: Islamic Studies and Social Journal, 2019)
Abstract: Research on the hadith will never run out. From ancient times until now the tradition has always attracted the interest of researchers to examine it. If the early days, hadith criticism is often intended to get the quality of hadith (s}ah}i>h}, h}asan, andd}aʻi>f), then in the next development the purpose of the study of hadith cannot be limited to that, but already must be broadened for the purpose of understanding and practice. In this case, various methods of criticism of the tradition of hadith emerged. One method of criticism that scholars have known from the past to the present is the "naskh" theory. Naskh's understanding according to Al-Asram is the same as the understanding expressed by classical scholars such as al-S}a>lih}, al-Zarqa>ni>, and al-Sudu>si>namely the abolition or appointment of a legal argument by the argument law that comes later. The Al-Asram epistemology is (1) the true nature of knowledge is based on history. (2) The main source of knowledge is revelation. (3) The method for acquiring knowledge is with history.As for the method taken to find out which mansukh traditions are: a) Takhri>j of the hadiths that have a theme. b) Criticism of sanad. c) Matan criticism, includes three things: 1) pay attention to the editor of matan (ʻilal and mudtarib), 2) pay attention to the context and situation as well as belief and 3) pay attention to the historical aspects. And (4) scientific validity of al-Hadith wa Mansukhuh narration uses coherence theory.الخلاصة : فمن المعروف، لا ينضب البحث في الحديث، لأن البحث في الحديث جذاب عند الباحثين.  وفي البداية، أنّ الأهداف من بحثها هو للوصول إلى جودة الحديث أي الصّحيح والحسن والضّعيف. ولكن مع تطوّر الزّمان، تطوّر الأهداف في بحث الحديث وهو للوصول إلى التفهيم والخبرة. وبالإضافة إلى ذلك، ظهر أنواع النّقد في متن الحديث، واشتهر هذا النقد عند علماء الحديث الماضي والحاضر، وسمي هذا النّقد بنظرية "النّسخ". وأما التعريف من النّقد عند الأسرام وأغلبية علماء الحديث كشيخ الصبح الصّالح والزرقاني والسّديسي هو رفع حكم شرعي سابق، بدليل شرعي متأخر عنه. وأما فلسفة العلوم عند الأسرام هو كما يلي: 1) التحديد لحقيقة العلوم الدراية نظرا إلى الرّواية. 2) مصدر المعرفة الأولي هو الوحي من الله غز وجلّ. 3) المنهج المستخدم للوصول إلى المعرفة هي بالرّواية. وبنسبة إلى الطريقة لمعرفة الأحاديث المنسوخ هي كما يلي: أ) القيام بتخريج الحديث الموضوعي. ب) القيام بنقد الأحاديث. ج) القيام بنقد متن الحديث. وأما الطريقة لنقد متن الأحاديث هي كما يلي:  1) الملاحظة بمضمون المتن (من حيث الإعلال والمضطرب). 2) الملاحظة بالسياق والأحوال والمخاطب. 3) الملاحظة نحو جانب التّاريخ. 4) الثّبات بعلوم ناسخ الحديث ومنسوخه باستخدام نظرية التماسك.Abstrak: Penelitian terhadap hadis tidak akan pernah habis. Sejak zaman dahulu hingga sekarang hadis selalu menarik minat para peneliti untuk menelitinya. Jika masa awal, kritik hadis seringkali ditujukan untuk mendapatkan kualitas hadis (s}ah}i>h}, h}asan,  dan d}aʻi>f), maka dalam perkembangan selanjutnya tujuan studi hadis tidak bisa dicukupkan sebatas itu saja, melainkan sudah harus meluas untuk tujuan pemahaman dan pengamalan. Dalam kasus inilah kemudian muncul berbagai metode kritik atas matan hadis. Salah satu metode kritik matan yang telah dikenal ulama dari dahulu hingga sekarang adalah teori “naskh”. Pengertian naskh menurut Al-Asram adalah sama dengan pengertian yang diungkapkan oleh para ulama klasik seperti Subhi al-S}a>lih}, al-Zarqa>ni>, dan al-Sudu>si> yakni  penghapusan atau pengangkatan suatu dalil hukum oleh dalil hukum yang datang belakangan. Adapun epistemologi Al-Asram adalah(1) hakikat ilmu pengetahuan yang benar adalah yang berdasar atas riwayat.(2) Sumber pengetahuan yang utama adalah wahyu. (3) Metode untuk memperoleh pengetahuan adalah bi al-riwa>ya>t. Adapun metode yang ditempuh untuk mengetahui hadis-hadis yang mansu>kh adalah: a) Takhri>j hadis-hadis yang setema. b) Kritik sanad. c) Kritik matan, meliputi tiga hal: 1) memperhatikan redaksi matan (ʻilal dan mud}t}arib), 2) memperhatikan konteks dan situasi serta mukha>t}ab dan 3) memperhatikan aspek sejarah. Dan (4) Validitas keilmuan Na>sikh al-H}adi>s| wa Mansu>khuh menggunakan teori koherensi.